Perancangan Cetakan Injeksi Plastik Two Plate Family Mold Dengan Slider untuk Produk Rahang Atas dan Rahang Bawah Perangkap Tikus Mekanik - Islameka, Metha; Media, Riona Ihsan; Gumelar, Julfiqi (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2024)
This research aims to produce a design for plastic injection molding equipment based on the upper and lower jaw products of mechanical mouse traps. Both products are printed in one mold called a family mold so they require plastic flow analysis to balance the plastic flow. The upper jaw product has a slider shape on each side. Calculations to ensure that the maxillary product can be ejected without damage are carried out. SolidWorks, TopSolid, and Autocad software are used for the process of designing mold families for upper and lower jaw products. The design results are documented in the form of layout drawings and section drawings. With the design process that has been carried out, all the list of requirements has been fulfilled, the design can function well, and technical documentation has been produced in the form of arrangement drawings and section drawings.